Weeding without Walking: A Mediated Approach to List-Based Deselection. Issue 2 (3rd April 2017) - McHale, Christopher; Egger-Sider, Francine; Fluk, Louise; Ovadia, Steven
ABSTRACT: Weeding an academic library is a complicated practice that tends to arouse debate. Despite these contentions, weeding is necessary to deal with the changing needs for space in many libraries. This article describes a holistic weeding project at LaGuardia Community College Library. It reviews several approaches the project team considered and draws on research, practice, and discussion to evaluate them. It concludes that weeding requires a balance between objective rules and professional judgment. The resulting workflow uses an interactive spreadsheet to automate some of the research work involved in deciding the fate of a book, allowing librarians to practice subjective weeding without walking through the stacks.